Meteorology and metrology: Evaluating parallels in the Ethiopic Parables of Enoch and 2 (Slavonic) Enoch. (December 2019) - Macaskill, Grant
This article will examine a set of distinctive conceptual and terminological combinations in the Ethiopic Parables of Enoch and the Slavonic 2 Enoch, associated with the meteorological elements and their angelic custodians/managers. These texts contain extended accounts of the storehouses (or treasuries) within which the elements are stored, and they exhibit a particular interest in how their angelic custodians distribute the elements to the earth; the imagery of distribution is, in turn, connected to metrological concepts informed by the imagery of a righteous balance (or scales). We will consider how other texts offer limited parallels to these combinations, a comparison that will help to illustrate the particularly close connection between the Parables of Enoch and 2 Enoch. The closest parallels are found in 3 Enoch, though here we will also see some striking developments that suggest the Ethiopic and Slavonic works preserve traditions from an earlier point of evolution. Some suggestive parallels will also be noted in works of Syrian origin, which might cast new light on the provenance or transmissional pathways of the Parables of Enoch and 2 Enoch.